TÉCNICAS DE APRENDIZAJE COOPERATIVO PARA LA ENSEÑANZA DE LA FÍSICA EN INGENIERÍA INDUSTRIAL - Ricardo Rizzo, José (2006)
The main results of a teaching experience applied to the module ‘Mechanics’ are presented. This subject is given to the first year in Industrial Engineering at the Universidad Europea de Madrid. The activity was highly skill-oriented, and it has represented 30% of the final qualification. Furthermore, it was implemented simultaneously to more traditional lectures. The students have decided the composition of the groups, as well as the subject of interest (connected to the module) and the planning for the activity, developed during the whole semester. Finally, they have orally communicated their works, followed by sessions of questions. The control meetings maintained by the professor have been revealed as vital elements for the experience. Another key aspect was the evaluation process, which has quantitatively considered several aspects by a weighted mean. When compared with the former year, the number of approved students was not changed significantly, but the amount of ‘given-up’ has greatly decreased. The satisfaction forms were highly well valued, especially concerning to the working in groups, the transparency of the evaluation method, and the possibility of choosing the subject to be studied. However, the students have manifested some difficulties, mainly in aspects such as planning and the size of the workgroups. The first results from the joined analysis of the forms and the detailed evaluations show an agreement between the learning feeling and the qualification, whilst there no seems to be any correlation with emotional factors.